Analisis Assessment Soal Ujian Sekolah Mata Pelajaran Bahasa Indonesia di SMP Negeri 17 Palu - Azhary, Azhary (Bahasantodea, 2016)
The question analysis is one of the evaluation activity, which purposed to the teacher. Because, in this case the teacher roles is important to make the question in each of subject that related with it. The question analysis activity is very important in the test which will be tested. The purposes are to know: 1. The quality of the question school observed from material aspect, construction and language, (2) The distribution the cognitif aspect of bloom taxonomy level which have measured at the question, (3) the quality of the question school exam at the indonesian subject observed from validity, difficulties level, distinguishing capacity, the effectively of key and swindlers, (4). The competence achievement level by the students participation that measured through school exam of indonesian subject with form of the question is multiple choice. The population and sample in this research is all of the ninth grade students at SMP Negeri 17 Palu. The data accumulation method which used in this research is documentation data like an archive the question test of school exam at indonesian subject class. The reasearch form which used is analysis of descriptive quantitative qualitative. Based on the result of the question aspect research which have some aspects, there are contents aspect (material), contruction aspect, and language aspect, there are unconformity about the question, that is for the material aspect there is 1 question or 2%, then construction aspect, there are 17 questions or 34%, and for language aspect, there is 1 question or 2%. So the questions could classify with well. Because from the total of the questions (50 questions), only 17 questions (38%) which classified bad or need to repair. Based on the result of the standard question difficulties level of school exam in indonesian subject at SMP Negeri 17 palu year study 2014/2015 from the total of the questions (50 Questions) were done by the students, include an easy category or the questions have an index difficulties < 0,30 or (56%) with the total of the question (28 questions item), for the medium category or have a moderate index difficulties ≥ 0,30 – 0,70 (38%) with the total of the question is 19 questions, and for the difficulties category or have an item index difficulties > 0,70 (6%) or only 3 questions item. The ninth grade students at SMP Negeri 17 palu state that this questions are easy, because almost all of the students can do it. So it needs to repair in the creating of the new question. In this case have a purpose to increasing human capacity sources more qualified